Visits by children to the UFTM itinerant planetarium: scientific dissemination in focus - Colombo Junior, Pedro Donizete (2021)
Experiences of scientific dissemination with children are configured as a field full of possibilities, announcing an open movement that can promote as many training opportunities for this audience. This paper describes the results of a qualitative, exploratory research that discusses the contact and previous knowledge in Astronomy of 193 students aged 6 to 11 years from the answers to a questionnaire in a visit to the Federal University of Triângulo Mineiro (UFTM) Itinerant Planetarium. This instrument focused on three axes: (i) a brief sociodemographic characterization; (ii) open question asking what a planetarium is and if the child had already visited a space outside the school in the year preceding the visit and (iii) Likert scale containing a level of agreement, on 5 levels, regarding statements related to themes of Astronomy. The results include information about the children's preparation for the visit, as well as their understanding of what a planetarium is and, more broadly, how science is configured and how to do it. Based on the results, educational implications are discussed which focused on analyzing the relationship established between scientific literacy, children and non-formal education through scientific dissemination.